Impact of Lactiplantibacillus plantarum on the fermentation quality, nutritional enhancement, and microbial dynamics of whole plant soybean silage - Meng, He; Xu, Yuwen; Wang, Lin; Wang, Jianping; Wang, Bing; Wu, Huimin; Hou, Donghui; Wang, Sui; Tong, Xiaohong; Jiang, Yan; Wang, Shaodong (Frontiers in Microbiology, 2025)
Soybean (Glycine max (L.) Merr.) is an important leguminous crop with rich nutrients and wide uses, yet soybean straw is often treated as waste in many areas without sufficient regard for its nutritional value. For the sustainable utilization of biomass resources, this study assessed the fermentation quality, microbial communities, and metabolites of whole plant soybean (WPS) silage with and without Lactiplantibacillus plantarum (LP) over different fermentation periods of 7, 15, 30, 60, and 90 days. With LP, there was a significant increase in dry matter (DM), crude protein (CP), and water-soluble carbohydrate (WSC) content of silage (p < 0.01) and a significant decrease in pH (p < 0.01). Incorporating LP into WPS silage significantly elevated lactic acid (LA) concentration, thereby improving fermentation quality. 16S rRNA gene sequencing revealed that LP inoculation significantly altered bacterial diversity and composition, notably increasing the relative abundance of Lactobacillus and promoting beneficial shifts in the microbial community during silage fermentation. Notably, LP treatment significantly promoted lysine biosynthesis, a key essential amino acid pathway, thereby contributing to the nutritional enhancement of the silage. Results showed that adding LP to WPS at ensiling can improve silage microbial community structure optimize metabolic processes, produce superior metabolites, and enhance the silage’s fermentation quality and nutritional value, after 60 days of fermentation. In summary, WPS silage with LP addition could serve as a promising strategy for preserving high-protein forage silage.